2022
DOI: 10.3389/fonc.2022.932337
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity in Pediatric Malignant Rhabdoid Tumors in Patients With Multi-Organ Involvement

Abstract: Rhabdoid tumors (RTs) of the brain (atypical teratoid/rhabdoid tumor; AT/RT) and extracranial sites (most often the kidney; RTK) are malignant tumors predominantly occurring in children, frequently those with SMARCB1 germline alterations. Here we present data from seven RTs from three pediatric patients who all had multi-organ involvement. The tumors were analyzed using a multimodal molecular approach, which included exome sequencing of tumor and germline comparator and RNA sequencing and DNA array-based methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, our patient developed extracranial metastases and treatment resistance, it may be better to consider rhabdoid predisposition syndrome, genetic and epigenetic profiling, and exploration of germline mutations in genes associated with rhabdoid predisposition syndrome (e.g., SMARCB1 or SMARCA4) could provide valuable insights. 20,28,29 Unfortunately, we could not perform such evaluations in the present case because the parents did not want them.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our patient developed extracranial metastases and treatment resistance, it may be better to consider rhabdoid predisposition syndrome, genetic and epigenetic profiling, and exploration of germline mutations in genes associated with rhabdoid predisposition syndrome (e.g., SMARCB1 or SMARCA4) could provide valuable insights. 20,28,29 Unfortunately, we could not perform such evaluations in the present case because the parents did not want them.…”
Section: Discussionmentioning
confidence: 97%
“…Gonadal mosaicism is thought to often account for inherited rhabdoid tumors, 8,10–12 but unusual reports of gain‐in‐function of SMARCB1 resulting in a similar phenotype have also been reported 13 . Case reports have found that not only do patients with synchronous rhabdoid tumors have varied methylation profiles, but also patients with metachronous rhabdoid tumors arising from RTPS, in which different DNA methylation patterns and copy number aberrations have been observed; these findings indicate that RTPS leads to non‐clonal formation of rhabdoid tumors 14,15 …”
Section: Genetic Basis Of Rtpsmentioning
confidence: 96%
“…13 Case reports have found that not only do patients with synchronous rhabdoid tumors have varied methylation profiles, but also patients with metachronous rhabdoid tumors arising from RTPS, in which different DNA methylation patterns and copy number aberrations have been observed; these findings indicate that RTPS leads to non-clonal formation of rhabdoid tumors. 14,15 Recent studies have characterized over 300 patients with ATRT and described prognostic molecular subdivisions (ATRT-SHH, ATRT-TYR, and ATRT-MYC) associated with the location of the tumor, average age of the patient, and specific genetic mutations. 16,17 More recently, ATRT samples were evaluated from a cohort of 325 patients from the Hospital for Sick Children in Toronto and 65 patients from the Children's Oncology Group (COG) study ACNS0333, and results validated the molecular subgroupings and revealed that the 16% of patients with germline mutations had a 4-year overall survival (OS) of only 20%.…”
Section: Genetic Basis Of Rtpsmentioning
confidence: 99%
“…INI1 codifies the INI1 protein (Integrase Interactor 1), a protein capable of interacting with the integrase protein of the human immunodeficiency virus. SMARCB1/INI1 is one of the core subunit proteins of the ATP-dependent SWI/SNF chromatin remodeling complex [47] and it has an important tumor suppressor action [51,52].…”
Section: Collecting Duct Carcinoma (Cdc)mentioning
confidence: 99%